Developments and innovation in carbon dioxide (CO₂) capture and storage technology. Volume 2, - Maroto-Valer, M. Mercedes (CRC Press ; Woodhead, 2010)
Carbon dioxide (CO2) capture and storage (CCS) is the one advanced technology that conventional power generation cannot do without. CCS technology reduces the carbon footprint of power plants by capturing, and storing the CO2 emissions from burning fossil-fuels and biomass. This volume provides a comprehensive reference on the state of the art research, development and demonstration of carbon storage and utilisation, covering all the storage options and their environmental impacts. It critically reviews geological, terrestrial and ocean sequestration, including enhanced oil and gas recovery, a.
Keywords: Carbon dioxide mitigation.; Carbon dioxide -- Storage.; Carbon sequestration.; Carbon dioxide.; elektronické knihy; electronic books